Ijtihad dalam Hukum Islam : Solusi atas Tantangan Zaman - Rayhan Kevin Rifaldy (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Ijtihad is one of the fundamental concepts in Islamic law that allows for interpretation and renewal of law in accordance with the development of the times. As a method of legal exploration carried out by scholars, ijtihad plays an important role in responding to various social, economic, and technological challenges that continue to develop. This article discusses the concept of ijtihad, its legal basis in Islam, and how its application can be a solution to contemporary problems that are not explicitly regulated in the Qur'an and Hadith. Through a qualitative method with a normative approach, this study reveals how ijtihad remains relevant in the modern Islamic legal system. The results of the study show that ijtihad carried out in a focused manner and based on the principles of maqashid al-shariah can be a flexible and dynamic solution in facing changes in the times. Thus, ijtihad acts as a bridge between the Islamic legal tradition and the demands of modern reality, allowing Islamic law to remain applicable and contextual in the lives of Muslims.